2013 8th International Workshop on Automation of Software Test (AST) 2013
DOI: 10.1109/iwast.2013.6595784
|View full text |Cite
|
Sign up to set email alerts
|

Automated scalability testing of software as a service

Abstract: Abstract-Scalability has been studied in several areas of Computer Science and scalability testing and evaluation of contemporary software systems is an active topic. However, most of the times, these activities are still performed in a predominantly ad hoc fashion. There are a few tools to automate this process, but they present several restrictions about what systems can be tested and how to evaluate scalability. In this paper, we introduce a flexible and extensible framework for automated scalability testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We plan to use the Scalability Explorer tool [13] to reflectively create rules for service compositions. The choice of a rule-based CEP engine will allow us to easily adopt a vast number of different reconfiguration strategies to our prototype.…”
Section: Resultsmentioning
confidence: 99%
“…We plan to use the Scalability Explorer tool [13] to reflectively create rules for service compositions. The choice of a rule-based CEP engine will allow us to easily adopt a vast number of different reconfiguration strategies to our prototype.…”
Section: Resultsmentioning
confidence: 99%
“…5 case studies are reported, using different operating systems and simulated services. Scalability Explorer, an automated framework for scalability testing is presented in [92], introducing scalability testing as TaaS through one experiment to evaluate a web service-based distributed matrix multiplication system hosted on Amazon EC2.…”
Section: ) Other Ways Of Testingmentioning
confidence: 99%
“…As a first step we are working on a software framework to automate scalability evaluation of distributed systems [25]. The intent is to provide a tool to simplify definition and execution of scalability experiments.…”
Section: Proposalmentioning
confidence: 99%
“…Common metrics proposed for scalability evaluation assume linear scal-ing [5,11,9,19,22], yet many use arbitrary thresholds for qualifying a system to be scalable [20]. Our aim is to provide components to perform automated analysis in order to verify if system performance remains the same when resource allocation is changed because of variatons in workload [25]. Our basis is deriving a model that captures the relation between workload and resource demand.…”
Section: Proposalmentioning
confidence: 99%